(untitled) - Jones, Leo (Cambridge, UK, 2000)
The Workbook covers all five FCE papers, including Listening and Speaking. It has a strong witing focus, with general composition or letter writing tasks included every unit.
Keywords: English language,English language; Examinations, questions, etc,Problems, exercises, etc